2021
DOI: 10.1038/s41598-021-88910-4
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine suppresses Parkinson’s disease like phenotypes induced by Synphilin-1 overexpression in Drosophila melanogaster by increasing tyrosine hydroxylase and dopamine levels

Abstract: It has been observed that there is a lower Parkinson’s disease (PD) incidence in tobacco users. Nicotine is a cholinergic agonist and is the principal psychoactive compound in tobacco linked to cigarette addiction. Different studies have shown that nicotine has beneficial effects on sporadic and genetic models of PD. In this work we evaluate nicotine’s protective effect in a Drosophila melanogaster model for PD where Synphilin-1 (Sph-1) is expressed in dopaminergic neurons. Nicotine has a moderate effect on do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…For instance, Esteves et al, 2017, demonstrated that nicotine effectively prevented prefrontal long-term potentiation and memory deficits induced by streptozotocin in AD, 53 whereas Carvajal-Oliveros et al, 2021, demonstrated that nicotine suppresses the PD-like phenotype induced by synphilin-1 overexpression through increased dopamine levels. 54 Similarly, a study concluded that the balance between dopamine and adenosine signals regulates the PKA/Rap1 pathway in spiny neurons, where D1R and A2AR agonist enhanced PKA-mediated Rap1 phosphorylation in vivo and in vitro . 55 Further, studies demonstrated that impaired GnRH production is directly linked to oxidative stress and mitochondrial dysfunction in neurons.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Esteves et al, 2017, demonstrated that nicotine effectively prevented prefrontal long-term potentiation and memory deficits induced by streptozotocin in AD, 53 whereas Carvajal-Oliveros et al, 2021, demonstrated that nicotine suppresses the PD-like phenotype induced by synphilin-1 overexpression through increased dopamine levels. 54 Similarly, a study concluded that the balance between dopamine and adenosine signals regulates the PKA/Rap1 pathway in spiny neurons, where D1R and A2AR agonist enhanced PKA-mediated Rap1 phosphorylation in vivo and in vitro . 55 Further, studies demonstrated that impaired GnRH production is directly linked to oxidative stress and mitochondrial dysfunction in neurons.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Gap junction (TUBB4B), GnRH signaling pathway (CDC42), and Rap1 signaling pathway (CDC42 and FGFR1) were critical pathways in which HUB proteins were involved and may be potential biological pathway targets for the AD and PD crosstalk. For instance, Esteves et al, 2017, demonstrated that nicotine effectively prevented prefrontal long-term potentiation and memory deficits induced by streptozotocin in AD, whereas Carvajal-Oliveros et al, 2021, demonstrated that nicotine suppresses the PD-like phenotype induced by synphilin-1 overexpression through increased dopamine levels . Similarly, a study concluded that the balance between dopamine and adenosine signals regulates the PKA/Rap1 pathway in spiny neurons, where D1R and A2AR agonist enhanced PKA-mediated Rap1 phosphorylation in vivo and in vitro .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Indeed, previous research in our laboratory showed that when heterozygous park 25 flies were treated with nicotine, they demonstrated improvements in climbing, flight, lifespan, and olfaction [13]. More recently, nicotine treatment in another Drosophila PD model also suppressed PD-like phenotypes [20].…”
Section: Introductionmentioning
confidence: 93%
“…Mutation of the Drosophila ortholog of the PRKN gene, parkin (park), leads to a tenable model of PD that has many similarities to PD patients: selective loss of dopaminergic neurons, decreased motor function, loss of olfaction, reduced lifespan, mitochondrial dysfunction, and others [13][14][15][16][17]. Another use of Drosophila PD models has been to identify potential therapeutics for PD, including, but not limited to, nicotine, acteoside, gastrodin, and other nutraceuticals [13,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, this result was observed only among smokers [ 134 ]. Indeed, some studies have found that smoking is associated with a reduced risk of developing PD as tobacco may regulate striatal activity through the dopaminergic system [ 135 , 136 ]. Thus, evidence linking vitamin B6 with the risk of developing PD should be interpreted with caution.…”
Section: Nutritive Patterns As a Predictor Of Early Detection Of Park...mentioning
confidence: 99%